HUBUNGAN GAYA KEPEMIMPINAN TERHADAP PSYCHOLOGICAL WELLBEING PERAWAT - Febriana Tri Kusumawati; Luky Dwiantoro; Devi Nurmalia (LPPM STIKES Muhammadiyah Kendal, 2022)
Leadership in the organization is the most important factor that can affect the achievement or failure of the goals and visions of the nursing organization's mission. Various types of leadership styles that change along with the times and the development of science in the field of nursing. The leadership style of nursing managers can affect the psychological well-being of nursing staff. The purpose of this study was to analyze previous research on leadership style on nurses' psychological well-being. This research used literature review study. This literature review starts from searching for articles in several journals, namely Google scholar, ResearchGate, Sciencedirect, pubmed, and proquest using keywords, then selecting articles according to inclusion criteria. Articles that have been selected are analyzed or synthesized data in tabular form. The articles obtained by using internet or online access methods, such as Google scholar, ResearchGate, Sciencedirect, pubmed, proquest with a publishing period of 2007-2021. The article in full text can be accessed with Indonesian and English journal articles. The review Method Conducted by collecting data or from various sources according to keywords and relevant sources. The result of the 9 articles analyzed, there are 4 articles that examine the relationship of leadership style to the psychological well-being of nurses. The application of different leadership styles is adjusted to the circumstances, goals and vision and mission of the nursing organization. The conclusion from 4 articles that examined the relationship of leadership style to the psychological well-being of nurses showed that all leadership styles were related to the psychological well-being of nurses.